"Parenting my parents": Perspectives of adult children on assuming and remaining in the caregiver's role - Jūratė Charenkova (Frontiers Media S.A., 2023)
BackgroundFamily caregivers are essential when responding to the long-term care needs of aging societies. The complex and multifaceted caregiver's role encompasses a unique set of challenges and strains, however, it can be a rewarding experience with many benefits and positive outcomes. Moreover, there is a link between the caregiver's wellbeing, quality of care, and the quality of life of the care recipient. Thus, the current study aimed to explore why adult children are assuming and remaining in the caregiver's role despite its challenges.MethodsResearch data was collected through the use of qualitative semi-structured interviews from September 2021 to July 2022. In total 16 Lithuanian and Italian caregivers were recruited through convenience/snowball sampling. The study utilized the constructivist grounded theory for data analysis and self-determination theory for data interpretation.ResultsAdult children's caregiving experiences revealed three themes related to the motivation to assume and continue with family care: (1) believing in the inherent value of family care; (2) making sense of the changing nature of caregiving; and (3) "making the best of it". Key motivational drivers of these decisions were associated with the satisfaction of the three basic psychological needs - autonomy, competence, and relatedness. Results show that finding meaning and making sense of the caregiving role when responding to a parent's increased care needs may result in positive caregiving experiences and outcomes even at rather low levels of the care recipient's autonomy.ConclusionCaregivers were able to experience family care as a meaningful and rewarding experience while acknowledging its challenges and limitations. Implications for family caregiving decisions and experiences, social policy, and future research are discussed in more depth in the paper.